Optical Studies of Transition Metal Chalcogenide MoSe2 Thin Films - T., Joseph Sahaya Anand; S., Shariza (Pushpa Publishing House, 2013)
Thin films of transition metal chalcogenides MoSe2 have been prepared by Electro deposition (ED) technique from high purity molybdenum and selenide materials. These materials are useful as a high temperature lubricant in the cryogenic rockets and other applications such as photo electrochemical (PEC) solar cells. X-ray diffraction (XRD) studies will confirm the structural characterization and crystallographic nature of these films. Scanning electron micrographs will reveal the information about their grain / micro structural properties. Compositional analysis by energy dispersive analysis by X-ray (EDX) will give their stoichiometric relationships. The optical results of these materials by UV-Vis spectrophotometer are finding with indirectly band gap energy.